The molecular basis for the immunogenicity ofCryptococcus neoformansmannoproteins - Stuart M. Levitz; Charles A. Specht (2006)
T-cell-mediated immunity is necessary for effective host defenses against infections caused by Cryptococcus neoformans. Clinical and experimental studies have identified a heterogeneous family of mannoproteins as critical cryptococcal antigens responsible for stimulating T-cell responses. The archetypal mannoprotein has a signal sequence, a functional domain, a serine/threonine-rich region and a site for attachment of a glycosylphosphatidylinositol anchor. Extensive O-mannosylation, which occurs at the serine/threonine region, facilitates recognition by mannose receptors on antigen-presenting cells, particularly dendritic cells. This results in efficient antigen uptake, processing and presentation to T cells. Inhibition of mannose receptors or deglycosylation of mannoproteins profoundly inhibits T-cell responses, demonstrating the crucial contribution of mannosylation to immunogenicity.